Pediatric Hospital Acquired Venous Thromboembolism - Witmer, Char M.; Takemoto, Clifford M. (Frontiers in Pediatrics, 2017)
Pediatric hospital acquired venous thromboembolism (HA-VTE) is an increasing problem with an estimated increase from 5.3 events per 10,000 pediatric hospital admissions in the early 1990s to a current estimate of 30-58 events per 10,000 pediatric hospital admissions. Pediatric HA-VTE is associated with significant morbidity and mortality. The etiology is multifactorial but central venous catheters remain the predominant risk factor. Additional HA-VTE risk factors include both acquired (recent surgery, immobility, inflammation and critical illness) and inherited risk factors. Questions remain regarding the most effective method to assess for HA-VTE risk in hospitalized pediatric patients and what preventative strategies should be implemented. While several risk assessment models have been published in pediatric patients, these studies have limited power due to small sample size and require prospective validation. Potential thromboprophylactic measures include mechanical and pharmacologic methods both of which have associated harms, the most significant of which is bleeding from anticoagulation. Standard anticoagulation options in pediatric patients currently include unfractionated heparin, low molecular weight heparin or warfarin all of which pose a monitoring burden. Ongoing pediatric studies with direct oral anticoagulants could potentially revolutionize the prevention and treatment of pediatric thrombosis with the possibility of a convenient route of administration and no requirement for monitoring. Further studies assessing clinical outcomes of VTE prevention strategies are critical to evaluate the effectiveness and harm of prophylactic interventions in children. Despite HA-VTE prevention efforts, thrombotic events can still occur and it is important that clinicians have a high clinical suspicion to ensure prompt diagnosis and treatment to prevent further associated harms.